2019
DOI: 10.1177/0145445519865170
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Children’s Feeding Behavior after Intensive Interdisciplinary Behavioral Treatment: Comparisons by Developmental and Medical Status

Abstract: This study examined changes in child mealtime behavior, diet variety, and family mealtime environment after intensive interdisciplinary behavioral treatment (IIBT) for 52 children referred to a day treatment feeding program. Children fell into three developmental status groups including autism spectrum disorder ( n = 16), other special needs ( n = 19), and no special needs ( n = 17), with some having no known medical problems ( n = 22) and some having gastrointestinal, cardiopulmonary, and/or endocrine-metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…All studies of inpatient or day programmes for physical illness with integrated input from psychologists (Cornwell, Kelly, & Austin, 2010; Hechler et al., 2014; Kemani, Kanstrup, Jordan, Caes, & Gauntlett‐Gilbert, 2018; Logan et al., 2012), psychiatrists (Uysal et al., 2019) and behavioural and occupational therapists (Bagnato & Mayes, 1986; Logan et al., 2012; Seiverling et al., 2020; Uysal et al., 2019) showed some significant improvements in either disease‐specific outcomes or behavioural symptoms including pain intensity (Hechler et al., 2014), glycaemic control (Uysal et al., 2019), feeding outcomes (Cornwell et al., 2010; Seiverling et al., 2020), behavioural functioning, anxiety and depression (Kemani et al., 2018; Logan et al., 2012) and developmental scores (Bagnato & Mayes, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…All studies of inpatient or day programmes for physical illness with integrated input from psychologists (Cornwell, Kelly, & Austin, 2010; Hechler et al., 2014; Kemani, Kanstrup, Jordan, Caes, & Gauntlett‐Gilbert, 2018; Logan et al., 2012), psychiatrists (Uysal et al., 2019) and behavioural and occupational therapists (Bagnato & Mayes, 1986; Logan et al., 2012; Seiverling et al., 2020; Uysal et al., 2019) showed some significant improvements in either disease‐specific outcomes or behavioural symptoms including pain intensity (Hechler et al., 2014), glycaemic control (Uysal et al., 2019), feeding outcomes (Cornwell et al., 2010; Seiverling et al., 2020), behavioural functioning, anxiety and depression (Kemani et al., 2018; Logan et al., 2012) and developmental scores (Bagnato & Mayes, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…By combining evidence-based behavioral interventions with occupational therapy skill building techniques related to oral, fine motor, and adaptive skills, the participants of this pilot program were successfully able to meet many of their feeding program goals. Previous research has found that behavioral feeding interventions that incorporate two or more disciplines have been effective in day treatment settings (Seiverling et al, 2020 ). The current evaluation of a bi-weekly interdisciplinary outpatient feeding intervention found that the combination of both psychology and occupational therapy services within this outpatient program was beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Research on interdisciplinary treatment has resulted in improved feeding behaviors of children with pediatric feeding disorders in day treatment programs and inpatient programs, including children with severe feeding difficulties that have resulted in the use of a feeding tube (Seiverling et al, 2020 ; Sharp et al, 2017 ; Volkert et al, 2021 ). Improved outcomes from interdisciplinary treatment programs have included decreases in inappropriate mealtime behaviors, decreases in caregiver stress, and increases in food volume and variety (Greer et al, 2008 ; Seiverling et al, 2020 ; Sharp et al, 2017 ). While positive outcomes from interdisciplinary feeding treatment from day treatment and inpatient programs have been prevalent in the feeding literature, there has been less research on the use of interdisciplinary approaches in more traditional outpatient settings.…”
Section: Interdisciplinary Treatmentmentioning
confidence: 99%
“…Strategies of reinforcement and non-avoidance were widely used in the included studies. Regarding reinforcement: (1) positive reinforcement was often used when children accepted the target foods (Johnson et al, 2015;Seiverling et al, 2020); (2) negative reinforcement was used to remove a stimulus and inhibit problematic behaviours (Johnson et al, 2015); and (3) differential reinforcement (DRA) of alternative behaviours was applied in three studies (Johnson et al, 2015;Sharp et al, 2009;Vazquez et al, 2019). Moreover, nonavoidance (i.e., escape extinction) served as a key strategy in eight of the included studies (Kuschner et al, 2017;Laud et al, 2009;Panerai et al, 2018;Seiverling et al, 2020;Sharp et al, 2009Sharp et al, , 2014Taylor et al, 2017;Vazquez et al, 2019).…”
Section: Behavioural Interventionmentioning
confidence: 99%